PREOROGENIC TECTONICS OF SOUTHERN MONGOLIA - Ruzhentsev S.V.; Badarch G. (My University, 1989)
The Paleozoic fold belt of southern Mongolia includes two systems, the Variscan (South Mongolian) and the Indosinian (Inner Mongolian or East Gobi). The first arose in the Early Carboniferous in the area of an old ocean and its continental margins, formed in the Ordovician on the Caledonian continent of northern Asia. The second developed in the Triassic on the Late Paleozoic arm of the Paleotethys. The Variscides and Indosinides of southern Mongolia have the same type of structure. Both are collision-produced systems with relicts of the crust and upper mantle of old oceanic, continental and transitional zones. The tectonic evolution of these two systems are summarized in this article.
Keywords: Paleozoic; Triassic; Ordovician; Carboniferous; Paleozoic; Mesozoic::Triassic; Paleozoic::Ordovician; Paleozoic::Carboniferous; Мезозой::Триасовая; Палеозой::Ордовикская; Палеозой; Палеозой::Каменноугольная